(untitled) (Modern Problems of Metallurgy, 2022)
Analysis of recent research and publications. The spread of electric current in the ore bath has been the subject of study for many years. Many scientists have performed mathematical modeling of electric fields of three-phase ore thermal furnaces, and also developed a method for conducting theoretical research using conformal mappings to determine the physical fields in the ore thermal melting furnace. Known mathematical models of energy distribution in the volume of the bath of the latter are based on the method of secondary sources, which has a number of disadvantages, in particular, complex integral equations that affect the volume of computational operations. Qualitatively, the electric field of the furnace is sufficiently illuminated, but the available information is not enough to accurately calculate the power, electrical transformations and temperatures at each point in the volume of the bath. The aim of the study. The above-mentioned mathematical models of the operation of the ore-thermal furnace describe only one process that takes place in it. Therefore, in complex modeling it is necessary to take into account all the processes and the relationship between them to obtain complete information about the power consumption of the furnace, the formation of melt and slag throughout the smelting of ferroalloys. Presentation of the main research material. The elements of the dynamic algorithmic model of operation of a round three-electrode ore thermal furnace are considered, which takes into account the specifics of electrical, thermal and chemical processes that are directly interconnected in the production of ferroalloys. Shows the complete generalized structure of such a model. The main purpose of its creation is the ability to control and influence the technological process to reduce the specific cost of electricity per unit of finished product. The algorithm is divided into basic blocks: input of initial parameters; division of the inner region of the furnace into elementary volumes (for calculations in them); determination of current flow paths; calculation of energy released in elementary volumes due to the passage of current through the charge; calculation of the temperature field of the bath; determination of the moment of self-ignition of coke; recalculation of the temperature field of the bath due to heat transfer processes; determining the amount of melt formed; calculation of the amount of charge that must be poured into the bath; output parameters of the furnace. The universality of this algorithm is the ability to interrupt the cycle of calculations under various conditions, such as: the value of the amount of electricity consumed (with time); the value of the formed melt (with time); and other. Conclusions. The model allows to stop melting and start draining of ferroalloys according to the predicted amount of formed melt, which in turn can reduce the melting time and the amount of electric energy consumed.